The Influence of Participative Leadership and Organizational Culture on Teacher Performance in Primary Schools - Heti Suryati; Sudarwan Danim; Azizatul Khairi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the influence of principals' participative leadership and school organizational culture on teacher performance in rural primary schools in Kinal District, Kaur Regency, Indonesia. Employing a quantitative survey design, data were collected from 44 teachers across four public primary schools using a census technique. Structured questionnaires measuring participative leadership, organizational culture, and teacher performance were analyzed using multiple linear regression with SPSS version 20. The results reveal that participative leadership has a significant positive effect on teacher performance (t = 3.482, p = 0.001), and organizational culture similarly demonstrates a significant positive effect (t = 2.967, p = 0.005). Simultaneously, both variables explain 47.9% of the variance in teacher performance (F = 18.742, p < 0.001, R² = 0.479). The study concludes that when principals actively involve teachers in decision-making and foster a collaborative, disciplined school culture, teacher performance improves substantially. The novelty lies in the integrated examination of both variables within the underexplored context of rural Indonesian primary schools, addressing a gap in national educational management literature. Practically, the findings recommend that principals adopt participative practices through formal and informal forums, strengthen organizational culture via shared values and teamwork, and prioritize these strategies particularly in resource-constrained rural settings. This study contributes to educational leadership and organizational behavior literature by empirically confirming the combined influence of participative leadership and organizational culture on teacher performance, providing evidence-based insights for school management policies, leadership training, and professional development initiatives in rural primary education.